PENERAPAN METODE EXPONENTIAL SMOOTHING PADA PERAMALAN PENJUALAN DALAM PENENTUAN KUANTITAS PRODUKSI ROTI (STUDI KASUS PERUSAHAAN ROTI DHIBA KENDARI) - Ni Putu Yuli Sukmarani; Statiswaty Statiswaty; Rahmat Ramadhan (semanTIK, 2016)
Dhiba bakery is a company that produce various  kinds of breads in large quantities. Today, they use an intuition method and experinence to decide how much bread they will produce. To optimize the amount of production, they need an application to manage marketing to produce bread for the next day. In the calculation process it used two methods, Exponential Smoothing and Mean Squared Error (MSE). Exponential smoothing is used to determine the amount of production for the next day. Meanwhile, Mean Squared Error (MSE) is used to calculate if there was an error. In this aplicatian, the database has four tables which consist of item data, production data, sales data, and forecasting data. Based on the forecast made in Application of  Exponential Smoothing Method in Sales Forecasting to determine bread production quantity. It will get a production forecast value of an item on a particular day in according input from the user. Keywords— Forecasting, Production, Exponential Smoothing, Mean Squance Error.